Implications of an RP-US FTA on the Philippine Financial Services Industry and the Philippine Economy - Leila Y. Calderon-Kabigting; Liberty S. Patiu (Philippine Institute for Development Studies (PIDS), 2006)
The paper discusses financial liberalization in the context of a proposed RP-US FTA. It discusses the state of the financial industry, in general, and also reviewed the US-Chile and US-Singapore FTAs to be able to arrive at the proposed provisions for the RP-US FTA. It also tackles the reforms that have to be undertaken in order to make the Philippine financial services industry globally competitive and be more prepared to embrace the opportunities of an FTA with the US.
Keywords: 330; capital markets; financial liberalization; financial services; electronic commerce (e-commerce); corporate governance; market access; cross-border transactions; foreign ownership limitations; international capital standards; harmonization of standards and practices; Internationale Wirtschaftsbeziehungen; Freihandelszone; Kapitalmobilität; Finanzmarktregulierung; Regulierung; Philippinen; USA